An evaluation tool for assessing coral restoration efforts - Schopmeyer, Stephanie; Galvan, Victor; Hernandez-Delgado, Edwin A.; Nava, Gabriela; D’Alessandro, Martine; Carne, Lisa; Goergen, Elizabeth; Viehman, Shay; Moulding, Alison; Lirman, Diego (Frontiers in Marine Science, 2024)
The ever-increasing need for coral restoration as a tool available to mitigate reef declines and aid in the recovery of lost ecosystem services requires improving restoration performance over time through an adaptive management framework to evaluate the status of restoration programs using uniform, consistent metrics. An evaluation tool, presented herein, allows restoration practitioners and managers to self-evaluate the robustness of each project and identify successful metrics, those metrics that need special attention, and changes to restoration strategies that can improve performance and aid recovery. This tool is designed to allow programs to track the progress of each key metric over time to assist in improving upon successes and learning from failures. The metrics within this restoration evaluation tool focus on published best-management practices and have resulted from extensive research conducted by restoration experts over the past 20 years. Common metrics of growth and survival are included, in addition to parameters vital to the operational success of restoration programs, such as coral reproduction, recruitment of associated reef taxa, increasing habitat for reef fisheries, and improving overall reef habitat. Five Caribbean restoration programs, each with at least 15 years of restoration experience, are presented as case studies. Each program was evaluated based on six restoration categories including: field-based nurseries, outplantings, programmatic management, education and outreach, event-driven restoration, and socioeconomic restoration. Category-specific metrics were scored with a binary scoring system and summarized using a stop-light indicator framework, where the resulting color/score indicates the operations tatus of the different program components (Scores >75% = green/successful; 50–74.9% = light green > yellow > orange/intermediate; <49.9% = red/sub-optimal). Composite scores may be used to evaluate individual projects, overall restoration programs, or even large-scale state of regional restoration plans. Overall, four of the five programs scored >75% indicating most of these programs are performing well, are versatile, well managed, and sustainable. Outside of environmental factors and large-scale disturbance events, many programs described resource limitations, including funding and staffing, as reasons for scoring low on some metrics. A holistic evaluation rubric incorporated into programmatic self-assessment can ensure that restoration projects and programs are working towards success and sustainability.